Mesoporous 45S5 bioactive glass: synthesis, in vitro dissolution and biomineralization behavior. Issue 44 (1st November 2017) - Kumar, Anil; Murugavel, Sevi; Aditya, Anusha; Boccaccini, Aldo R.
Abstract : The development of a new generation of biomaterials includes a sol–gel process to obtain glass foams, which is a well established method for CaO–SiO2 –P2 O5 compositions, but is not yet recognized for Bioglass® containing sodium oxide. Abstract : The development of a new generation of biomaterials includes a sol–gel process to obtain glass foams, which is a well established method for CaO–SiO2 –P2 O5 compositions, but is not yet recognized for Bioglass® containing sodium oxide. In this study, we report, for the first time, the synthesis of a mesoporous 45S5 bioactive glass with superior textural characteristics and its in vitro dissolution and biomineralization behavior. Wormhole-like bioactive mesostructured 45S5 glass has been synthesized by an acid assisted sol–gel method followed by an evaporation induced self-assembly process. The virgin mesoporous 45S5 bioactive glass has been characterized by various analytical methods before and after soaking in simulated body fluid (SBF). The factors affecting the glass formation have been discussed in terms of the critical micelle concentration (CMC) at a particular temperature followed by a specified time interval. In vitro studies on the mesostructured 45S5 glass sample reveal the rapid formation of carbonated hydroxyapatite (HCA) with nano sized crystals. The mesostructured glass showed an excellent cell proliferation response without toxicity up to the concentration of 50 μg ml −1 . Furthermore, we show that the 45S5 glass with superior textural parameters is extremely useful within the family of bioactive materials as it has accelerated formation kinetics of the apatite phase as compared to other bioactive glass compositions.